Effect of E-Filling System Application with Internet understanding of Taxpayer compliance as Moderation Variable in North Karawang North Tax Office - Nadeak, Thomas; Marliani, Sari; Henry Wijaya, John (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the Effect of E-filling Implementation with internet understanding of Karawang City Taxpayer compliance. The sample used in this study were 100 respondents. This questionnaire was tested with a validity test, a reliability test. The classic test used was the Normality Test, Multi-collinearity Test, Linearity Test. Hypothesis Test using Multiple Linear Regression, T Test, F TestFrom the research results above the application of the E-filling system 0.520> 0.05 does not significantly influence partially on internet understanding. Taxpayer Compliance 0.025